Effect of management system and pedoclimatic factors on Fusarium and Didymella communities associated with pea (Pisum sativum) roots in Germany - Adnan Šišić; Jelena Baćanović-Šišić; Harald Schmidt; Maria R. Finckh (Scientific Reports)
Abstract From 2016 to 2019, 128 organic and conventional spring and winter pea fields in Germany were surveyed to determine the effects of cropping history and pedo-climatic conditions on pea root health, the diversity of Fusarium and Didymella communities and their collective effect on pea yield. Roots generally appeared healthy or showed minor disease symptoms despite the frequent occurrence of 4 Didymella and 14 Fusarium species. Soil pH interacted with the occurrence of the Fusarium oxysporum species complex (FOSC) and F. tricinctum that correlated with reduced or increased soil pH values, respectively. While legumes in the cropping history or reduced time between legumes correlated with occurrence of D. pinodella and to a lesser degree with the members of the F. solani species complex (FSSC), the reverse was true at least in organic spring peas for F. redolens. Only in conventional systems increased root infections with F. redolens and the FSSC were linked to root rot incidence whereas yields negatively correlated with the FOSC and positively with F. tricinctum isolation frequencies. Overall, this study shows that pea root rot pathobiome is rather stable and that the damage caused is mostly due to the interaction with environmental conditions.